2010
DOI: 10.1177/1934578x1000500812
|View full text |Cite
|
Sign up to set email alerts
|

Geranylated Flavonols from Macaranga Rhizinoides

Abstract: Two geranylated and methylated flavonol derivatives, macarhizinoidins A (1) and B (2), along with a known phenolic compound methyl 4-isoprenyloxycinnamate (3), have been isolated from the methanol extract of the leaves M. rhizinoides. The structures of these compounds were identified based on their spectroscopic data. On cytotoxic evaluation against murine leukemia P-388 cells, compounds 1-2 showed IC 50 values of 11.4 and 13.9 μM, respectively, while compound 3 was inactive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
9
0
2
Order By: Relevance
“…The known compounds were identified as denticulatain D (2) [9], bonannione A (3) [13,14], diplacol (4) [14], macarangin (5) [5,15], 3-O-methylmacarangin (6) [5,15], 5,7,3',4'-tetrahydroxy-3-methoxy-6-geranylflavone (7) [9], 3,5,7,3',4'pentahydroxy-6-geranylflavonol (8) [9], macarhizinoidin A (9) [16], robipseudin A 10) [17], denticulatain E (11) [9], 8-dimethylallylisosakuranetin (12) [18], 4'deprenylmappain (13) [19], deheiculatin H ( 14) [20], poilaneic acid (15) [21], derivative phaseic acid ( 16) [22], taraxerone (17) [23,24], epitaraxerol ( 18 Since prenylated flavonoid and prenylated stilbenes from Macaranga genus are reported to have potent cytotoxic activities [26,27], the cytotoxic activities of compound 1-13 were evaluated against seven cancer cell lines: MCF-7 (human breast cancer cells), HepG-2 and Hep3B (human liver cancer cells), Lu-1 (human lung adenocarcinoma cells), Hela (human cervical cancer cells), KB (human epithelial carcinoma cells), A549 (human non-small cell lung cancer) by MTT-based colorimetric assay [28,29]. The results showed that compound 1 showed moderate cytotoxic activity against A549 and Hela cell lines with IC50 values of 16.0 and 36.9 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The known compounds were identified as denticulatain D (2) [9], bonannione A (3) [13,14], diplacol (4) [14], macarangin (5) [5,15], 3-O-methylmacarangin (6) [5,15], 5,7,3',4'-tetrahydroxy-3-methoxy-6-geranylflavone (7) [9], 3,5,7,3',4'pentahydroxy-6-geranylflavonol (8) [9], macarhizinoidin A (9) [16], robipseudin A 10) [17], denticulatain E (11) [9], 8-dimethylallylisosakuranetin (12) [18], 4'deprenylmappain (13) [19], deheiculatin H ( 14) [20], poilaneic acid (15) [21], derivative phaseic acid ( 16) [22], taraxerone (17) [23,24], epitaraxerol ( 18 Since prenylated flavonoid and prenylated stilbenes from Macaranga genus are reported to have potent cytotoxic activities [26,27], the cytotoxic activities of compound 1-13 were evaluated against seven cancer cell lines: MCF-7 (human breast cancer cells), HepG-2 and Hep3B (human liver cancer cells), Lu-1 (human lung adenocarcinoma cells), Hela (human cervical cancer cells), KB (human epithelial carcinoma cells), A549 (human non-small cell lung cancer) by MTT-based colorimetric assay [28,29]. The results showed that compound 1 showed moderate cytotoxic activity against A549 and Hela cell lines with IC50 values of 16.0 and 36.9 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As a part of our study in the search for new anticancer compounds from Vietnamese medicinal plants, the ethyl acetate extract of the fruits of M. denticulata was found to inhibit the growth of KB cancer cell line. In this paper, we report the isolation and structural elucidation of a new modified geranyl-type side chain substituted flavonoid, 6-(8″-hydroxy-3″,8″-trimethyl-oct-2″-enyl)-kaempferol (1) from the fruits of M. denticulata along with 11 prenylated flavonoids (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), a prenylated stilbene (13), two diterpenoids (14 and 15), a sesquiterpenoid (16), and two triterpenoids (17 and 18) from the fruits of Macaranga denticulata Muell. Arg.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous reports, we disclosed the presence of isoprenylated and geranylated flavonoids [1][2][3][4], and phenolic derivatives containing an irregular sesquiterpenyl side chain, from Indonesian Macaranga [3,5]. In continuation of these chemical investigations, we have examined M. recurvata Gage and succeeded in isolating two new dihydroflavonols, trivially named as macarecurvatins A (1) and B (2), together with the known compounds 6,8-diisoprenylaromadendrin (3) [6], glyasperin A (4) [7], and broussoflavonol F (5) [8].…”
mentioning
confidence: 93%
“…Some of these compounds have also been tested for a number of biological properties, including anticancer, antioxidant, and anti-inflammatory activities [1]. Recently, our laboratory has succeeded to isolate a number of these phenolic compounds, including monoprenylated dihydrochalcones and flavanones from M. trichocarpa [2,3]; geranylated and farnesylated dihydroflavonols from M. gigantea, M. pruinosa, and M. rhizinoides [4][5][6]; prenylated dihydroflavonols from M. lowii and M. recurvata [7,8]; and phenolic derivatives with an irregular sesquiterpenyl side chain from M. pruinosa [9]. As further work on the phytochemistry of this genus, in this paper we report the presence of prenylated dihydrophenanthrenes, trivially named macajavanicins A-C (1-3) (Fig.…”
Section: Introductionmentioning
confidence: 99%